Self‐sealing thermoplastic fluoroelastomer enables rapid fabrication of modular microreactors. Issue 7 (5th February 2021) - McMillan, Alexander H.; Mora‐Macías, Juan; Teyssandier, Joan; Thür, Raymond; Roy, Emmanuel; Ochoa, Ignacio; De Feyter, Steven; Vankelecom, Ivo F. J.; Roeffaers, Maarten B. J.; Lesher‐Pérez, Sasha Cai
Abstract: A novel fluorinated soft thermoplastic elastomer (sTPE) for microfluidics is presented. It allows the rapid fabrication of microfluidic devices through a 30‐second hot embossing cycle at 220°C followed by self‐sealing through simple conformal contact at room temperature, or with baking. The material shows high chemical resistance, particularly in comparison to polydimethylsiloxane (PDMS), to many common organic solvents and can be rapidly micropatterned with high fidelity using a variety of microfluidic master molds thanks to its low mechanical stiffness. Self‐sealing of the material is reversible and withstands pressures of up to 2.8 bar with room temperature sealing and four bar with baking at 185°C for 2 hours. The elastomeric, transparent sTPE exhibits material characteristics that make it suited for use as a microreactor, such as low absorption, surface roughness and oxygen permeability, while also allowing a facile and scalable fabrication process. Modular microfluidic devices, leveraging the fast and reversible room temperature self‐sealing, are demonstrated for the generation of water droplets in a toluene continuous phase using T‐junctions of variable size. The sTPE offers an alternative to common microfluidic materials, overcoming some of their key drawbacks, and giving scope for low‐cost and high‐throughput devices for flow chemistry applications. Abstract : A soft thermoplastic fluoroelastomer for microfluidics is introduced. The thermoplastic exhibits good chemical resistance to organic solvents and can be micropatterned using rapid hot embossing and made into microfluidic devices with its self‐sealing property. Key material characterization data is presented and a modular microfluidic platform is demonstrated, which leverages facile self‐sealing to enable interchangeable device modules for "plug‐and‐play" microfluidic operation.